A disproportional increase in lower priority mental health-related calls to New Zealand Police between 2009 and 2016. (27th May 2020) - Li, Judy; Newcombe, Rhiannon; Hendy, Ross; Walton, Darren
ABSTRACT: Internationally police agencies reported steady increases in mental health-related demand for service. This increase in demand has significant implications on the resourcing and training needs of both frontline and call centre staff. Mental disorders comprise a broad range of psychological conditions and therefore are difficult to define concisely. In police's operational environment, frontline and contact centre staff are often required to make decisions quickly based on the limited information they have; this practice is not unique to mental health-related events. The process of coding an event could be based on perception, prior contact with police, and/or other information available at the time. Due to the ambiguous definition of 'mental health' in the police context, it is important to understand the characteristics of events categorised as 'mental health' to enable adequate deployment and practice of police. To do this, this analysis examines the characteristics of mental health-related calls received by New Zealand Police between 2009 and 2016; these calls were assigned the code 'mental health' at event closure. The results indicated a 9% increase in this call type per year on average. The urgency of these calls for police attendance was approximated using two measures: (1) priority of calls at closure and (2) result code (i.e. follow-up actions). Both measures indicated a disproportional increase in lower-priority calls. This finding may suggest a general change in service demand and expectation of police's role in mental health, and have implications on police's service model and cross-agency collaboration to support people with mental disorder.